A new Allium species from section Molium from Israel: A. akirense (Amaryllidaceae) - Friesen, Nikolai; Fragman-Sapir, Ori (Phytotaxa, 2014)
As part of the phylogenetic revision of the Eurasian representatives of the subgenus Amerallium we have discovered a new Allium species (section Molium) in Israel, related to A. qasyunense. It is described here as Allium akirense, based on living plants and recent herbarium specimens. Independence of the new species is confirmed by morphological and ecological features, and also by molecular ones. To learn more about the phylogenetic relationships within a group of closely related species of section Molium, we used maximum parsimony and Bayesian analyses of combined nuclear (ITS—internal transcribed and ETS—external transcribed spacers of rRNA genes) and chloroplast (rpl32–trnL intergenic spacer) dataset of 7 taxa. Discussion on geographic distribution, conservation status and habitat is provided, as well as an identification key including the closest related species.